The The relationship between mother’s knowledge with the incidence of diarrhea : A cross sectional study in toddlers - Sartika, Epi; Suryani, Suryani; Wulan, Susilo (Community Research of Epidemiology (CORE), 2022)
Diarrhea is the most common cause of infant death. The mother is the person closest to the child and has an important role in maintaining and maintaining the health of the child, so a good mother’s knowledge is needed to prevent diarrhea in children. This study aims to study the relationship of mother’s knowledge with the incidence of diarrhea in infants in the working area of Tebing Tinggi Health Center, Empat Lawang District. The design used in this study is an analytic survey design that uses a cross sectional study design. The population in this study were all mothers who have toddlers aged 0-5 years who came for treatment at Tebing Tinggi Health Center, Empat Lawang in July-August 2019. Sampling in this study used 81 Simple Random Sampling techniques. This research uses primary data and secondary data. Data analysis was performed univariately and bivariately. The results showed there is a significant relationship between the relationship between maternal knowledge about diarrhea and the incidence of diarrhea in infants in the working area of Tebing Tinggi Health Center, Four Lawang Regency, with a moderate relationship category. It is expected that the puskesmas can provide health education to the community about diarrhea through counseling activities, distributing leaflets and nut book explaining diarrhea